Debatforum: Hvordan erindres folkehøjskolens historie? - Korsgaard, Ove (Grundtvig-studier, 2007)
Debatforum[Forum for debate]In the Forum for debate, readers are invited to respond to issues raised, or to raise new issues relative to the field of Grundtvig studies. Items submitted, preferably in the form of an article, may be of any reasonable length and in any of the languages usually accepted by the journal. Contributions in Grundtvig-Studier 2007 are written by Ove Korsgaard and P.l Bødtker Walstad.Unfortunately, due to a mistake during the editing of Professor, dr. p.d. Ove Korsgaard’s contribution “ Hvordan erindres folkehøjskolens historie?” in Grundtvig-Studier 2006, certain sections were misplaced. As this may have caused confusion to the readers, we are reprinting the contribution in its original form. The editors of Grundtvig-Studier 2006 would like to apologise for the misprint. Debatforum: Hvordan erindres folkehøjskolens historie?[Forum for debate: How do we recall the history of the Danish folk highschool?]By Ove Korsgaard It is a well-recognised phenomenon in the process of historical recall that both deliberate manipulation and less conscious selectivity of what is remembered and what forgotten may distort the true record of events, even though the distorted record may then become the basis upon which the present generation shapes its prospect of the future. A close reexamination of the historical and constantly evolving struggle between competing ideals in the folk-highschools from Grundtvig’s day onwards reveals that unhistorical notions of pure and miscegenated educational models have established themselves. This distortion of the true history of the evolution of these schools may now be obstructing the clear-headed and pragmatic reassessment of its future that the folk-highschool movement is currently having to confront.